Significance of EGFR and PTEN Expression and PLR and NLR for Predicting the Prognosis of Epithelioid Malignant Peritoneal Mesothelioma - Yufei Liang; Guoqi Zheng; Wenjie Yin; Hui Song; Chunying Li; Liang Tian; Dongliang Yang (Gastroenterology Research and Practice)
Objective. The aim of our study was to investigate the expression of EGFR and PTEN in tissues and measure the serum platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) to evaluate the prognostic factors of patients with epithelioid malignant peritoneal mesothelioma (MPeM). Methods. 33 patients of pathologically diagnosed epithelioid MPeM tissues were analyzed using immunohistochemistry to detect EGFR and PTEN; the PLR and NLR were determined by using a routine blood test. We analyzed the relationships of these markers to age, sex, asbestos exposure, elevated platelet count, ascites, and clinical stage. Results. EGFR and PTEN expressions were positive in 22 (66.67%) and 7 (21.21%) epithelioid MPeM patients, respectively. However, these two markers as well as PLR and NLR were not significantly associated with age, sex, asbestos exposure, elevated platelet counts, ascites, and clinical stage (P>0.05). The correlation between EGFR and PTEN was negative (r=−0.577, P<0.001), but the correlation between NLR and PLR was positive (r=0.456, P=0.008). The median survival of all patients was 6 months. In univariate analysis, PTEN (P<0.001), PLR (P=0.014), and NLR (P=0.015) affected the overall survival. Multivariate analysis revealed that PTEN and PLR were validated as predictive for overall survival of epithelioid MPeM (HR=0.070, P=0.001, and HR=3.379, P=0.007, respectively). Conclusion. On the basis of these results, it is suggested that PTEN and PLR are risk factors for the prognosis of epithelioid MPeM, which may be targets for selective therapies and improve the outcomes of patients with epithelioid MPeM.